Regulatory requirements of the European Medicines Agency for evaluation of bioequivalence of modified-release medicinal products - D. P. Romodanovsky; N. N. Eremenko; D. V. Goryachev (Регуляторные исследования и экспертиза лекарственных средств)
There are no specific requirements and recommendations in the Russian Federation for evaluation of bioequivalence of modified-release medicinal products. Until recently, modified-release products were regulated in a similar manner as immediate-release products, which is unacceptable considering the active ingredient release profile and its pharmacokinetics. The modified release characteristics require a more complex approach to the assessment of equivalence of generic medicines as compared with the reference product. The number of parameters to be assessed and the scope of testing depend on many factors (release mechanism, specific features of the dosage form, linearity of pharmacokinetics, potential for ingredient accumulation, dependence on food intake, dose-dumping effects, and the number of dosage strengths to be registered). The aim of this paper was to develop recommendations for the national procedure of modified-release products authorisation based on the analysis of international regulatory experience in this field. The paper reviews the current European Medicines Agency (EMA) guidelines on evaluation of bioequivalence of generic modified-release dosage forms for oral use that were taken as a basis for the development of Eurasian Economic Union regulations on bioequivalence assessment. The analysis of the above-mentioned documents made it possible to develop recommendations for the national procedure of modified-release products authorisation. In the case of modified-release products for oral use it is recommended to perform bioequivalence studies by comparing the test product with the reference product. The authors developed a procedural algorithm for bioequivalence studies of modified-release medicinal products.